2016
DOI: 10.1007/s11356-016-7950-0
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effect on physiological responses of the tolerant Chlorophyta specie Picocystis sp. isolated from Tunisian wastewaters

Abstract: This study aims to investigate the effects of different concentrations of cadmium (Cd) (0-800 μM) on the growth, the photosynthetic performance, and the biochemical parameters of the Chlorophyta Picocystis sp. during 3 and 9 days. Results showed that this exposure did not inhibit the Picocystis growth during the first 3 days of treatment. Growth inhibition did not exceed 53%, which was recorded at high Cd concentrations (800 μM) after nine exposure days. Moreover, no inhibitory effect on the Picocystis sp. pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It has to be emphasized that, for both studied species, the BPA IC 50 values were much higher than the BPA concentrations measured in the isolation sites, which were lower than the HPLC limit detection (data not shown). This fact has been observed in many Chlorophyta species exposed to several contaminants such as antibiotics and herbicides (Costas et al 2001;Lopas-Rodas et al 2007;Marvá et al 2010), algaecides (Garcia- Villada et al 2004), and heavy metals (Ben Ali et al 2017). The continuous exposure to low contaminant concentrations could induce an inherent resistance probably through the selection of rare spontaneous mutations (García-Balboa et al 2013).…”
Section: Effect Of Bpa On Microalgae Growthmentioning
confidence: 87%
See 1 more Smart Citation
“…It has to be emphasized that, for both studied species, the BPA IC 50 values were much higher than the BPA concentrations measured in the isolation sites, which were lower than the HPLC limit detection (data not shown). This fact has been observed in many Chlorophyta species exposed to several contaminants such as antibiotics and herbicides (Costas et al 2001;Lopas-Rodas et al 2007;Marvá et al 2010), algaecides (Garcia- Villada et al 2004), and heavy metals (Ben Ali et al 2017). The continuous exposure to low contaminant concentrations could induce an inherent resistance probably through the selection of rare spontaneous mutations (García-Balboa et al 2013).…”
Section: Effect Of Bpa On Microalgae Growthmentioning
confidence: 87%
“…A volume of 250 mL of each treatment was centrifuged and collected; cells were mixed with 2 mL of 0.1 M sodium phosphate buffer (pH 7.0) containing 0.1 mM Na 2 EDTA and 1 mM ascorbic acid and ruptured by sonication three times for 30 s (Ben Ali et al 2017). The homogenate was then centrifuged at 10,000×g for 10 min at 4 °C.…”
Section: Lipid Peroxidation and Antioxidant Activitiesmentioning
confidence: 99%
“…P. salinarum is a particularly important species when regarding phytoplankton in saline environments. The species was described only in 2000 (Lewin et al, 2000) from a saline pond at the San Francisco Salt Works and later was recorded from a number of saline environments across almost all continents (Inner Mongolia- Hollibaugh et al, 2001; Mono lake USA Roesler et al, 2002;Fanjing et al 2009; North Africa- Rihab et al, 2017;Peru-Tarazona Delgado et al, 2017;India-Krienitz, 2018; Mayotte Island, Indian Ocean- Cellamare et al, 2018;Bernard et al, 2019).…”
Section: Salinitymentioning
confidence: 99%
“…The cells are spherical and non-flagellated, 2-3 μm in size, and display a distinct set of pigments consisting of carotenoids alloxanthin, diatoxanthin, and monadoxanthin along with chlorophyll a and b. P. salinarum was first reported from a saline pond (100‰ salinity) at the San Francisco Salt Works, California, United States (Lewin et al, 2000;Lopes dos Santos et al, 2016). Since then, different Picocystis strains have been reported from extremely saline waterbodies, saline-soda lakes across the four continents, flourishing in extreme environmental conditions of pH up to 11, salinity up to 300‰ and temperature up to 60°C (Krienitz et al, 2012;Ali et al, 2017;Ouada et al, 2018;Pálmai et al, 2020). Krienitz et al (2012) states that "Picocystis salinarum from saline inland waters represents a link between marine and freshwater habitats from both an ecological and a phylogenetic point of view and is therefore of great interest. "…”
Section: Introductionmentioning
confidence: 99%
“…Krienitz et al (2012) states that "Picocystis salinarum from saline inland waters represents a link between marine and freshwater habitats from both an ecological and a phylogenetic point of view and is therefore of great interest. " Also, recent reports have suggested that Picocystis may have potential biotechnological applications from wastewater treatment (Ali et al, 2017;Ouada et al, 2018), to biofuel production (Wang et al, 2014;Delgado et al, 2021). In spite of demonstrating such unique environmental adaptations, flourishing and out competing other primary producers at extreme salinities and influencing the food web dynamics (Krienitz and Kotut, 2010), P. salinarum has gone unreported in most of the culture independent metagenomic studies of saline ecosystems all over, indicating the lack of information about this organism on molecular level.…”
Section: Introductionmentioning
confidence: 99%